Depression Partially Mediates the Association Between Binge Eating Disorder and Health-Related Quality of Life - Singleton, Christopher; Kenny, Therese E.; Hallett, Darcy; Carter, Jacqueline C. (Frontiers in Psychology, 2019)
Research has found that individuals with binge eating disorder (BED) report significantly worse health related quality of life (HRQL) than those without eating disorders. Studies indicate that the association between BED and HRQL is largely accounted for by psychopathology (e.g., depression), rather than physiology (e.g., increased body mass index). However, to our knowledge, no study has yet investigated whether mental health symptoms could potentially mediate the relationship between BED and HRQL. To this aim, the present study compared a sample of adults who met DSM-5 criteria for BED (n = 72) recruited from the community for a treatment trial and a community sample of individuals with no history of an eating disorder (NED; n = 79). Participants completed self-report measures of HRQL (Short-Form 6D), eating disorder psychopathology (Eating Disorder Examination Questionnaire), and anxiety and depressive symptoms (Brief Symptom Inventory). Consistent with previous findings, the BED group reported significantly worse HRQL than the NED group after controlling for age, body mass index, anxiety, depression, and eating disorder psychopathology. Moreover, depression partially mediated the relationship between BED diagnosis and HRQL. These results suggest that lessened HRQL may be partly explained by comorbid symptoms of depression in BED. Clinicians may find it helpful to specifically assess and treat depression in BED as a means of enhancing patients’ well-being. Future research should replicate these findings using longitudinal data that will allow for causal inferences.